The Effect of Tax, Tunneling Incentive, and Firm Size on Corporate Transfer Pricing Decisions: Evidence from Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) in 2021–2023 - Astri, Nindhi Lita; Ramadhany, Andi Auliya; Laili, Nur Isra (Politeknik Negeri Madiun, 2025)
This study aims to examine the effect of tax, tunneling incentive, and firm size on corporate transfer pricing decisions in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Transfer pricing is a strategy used by multinational companies to minimize tax liabilities through transactions with related parties. Various factors may influence such decisions, including tax policy, the interests of controlling shareholders, and company size.This study adopts a quantitative method with a multiple linear regression approach. Secondary data were collected from the financial statements of manufacturing firms listed on the IDX. The independent variables are tax, tunneling incentive, and firm size, while the dependent variable is the decision to engage in transfer pricing.The findings reveal that tax has a positive but statistically insignificant effect on transfer pricing, suggesting that tax may influence decisions, but its impact is not strong. Tunneling incentive has a negative and significant effect, indicating that higher incentives lead to less transfer pricing activity, possibly due to other profit-shifting mechanisms. Firm size shows a negative but insignificant effect, meaning it does not play a major role in transfer pricing decisions in this context.